SISTEM DETEKSI NOMINAL UANG KOIN BERBASIS COIN ACCEPTOR - Susilawati, Ratna; Kinaya, Haula; Irwan, Irwan; Ariesta Sandra, Yuke Mareta (Prosiding Seminar Nasional Inovasi Teknologi Terapan, 2025)
Saving money is an important but often overlooked habit, especially when it comes to small coins. Many people consider coins to be impractical and worthless, so their existence tends to be overlooked. This research develops a digital piggy bank system based on coin acceptor and ESP32 microcontroller that is able to detect the nominal value of coins automatically. The system not only calculates the total amount of money inserted, but also displays the nominal fraction inserted and the total amount of coins inserted directly through a Liquid Crystal Display (LCD) and sends the data to a digital application, namely telegram bot, using a Wi-Fi connection. This device is able to detect five types of rupiah coins: Rp100, Rp200, Rp500 (two types), and Rp1,000. The addition of the IoT feature allows users to monitor the amount of savings remotely in real-time. The test results show that the device can identify the nominal accurately and run stably. This prototype is expected to increase interest in saving, especially among children and adolescents, with an educational approach. The limitation of this tool is the dependence on Wi-Fi connection, the system will not be active without the network.